PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 4 SOLOK SELATAN - Putri, Hervania Nanda; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2019)
ABSTRACTThis article aims to describe the effect of the problem based leaerning model on explanatory text writing as found on eight grade at SMP Negeri 4 Solok Selatan.The type the research is quantitative with the experimental method. There are three results found from the research, these are (1) eight grade students expansive writing skills as found at SMP Negeri 4 Solok Selatan before they were tought using the problem based learning model it were already in a qualitied stage with the average valve is 70,67, (2) eight grade students explanatory writing skills of SMP Negeri 4 Solok Selatan after being tought using the problem based learning model is in a better qualified stage with the average valve is 86,86, and (3) eight grade student explanatory writing skills of SMP Negeri 4 Solok Selatan using the problem based learning model have been in a good stage even without using the problem based learning model.Â Kata Kunci: Pengaruh, Model Problem Based Learning, Keterampilan Menulis Teks Eksplanasi